2018 21st International Conference on Information Fusion (FUSION) 2018
DOI: 10.23919/icif.2018.8455236
|View full text |Cite
|
Sign up to set email alerts
|

An Implementation of the Poisson Multi-Bernoulli Mixture Trajectory Filter via Dual Decomposition

Abstract: The Poisson multi-Bernoulli mixture (PMBM) and the multi-Bernoulli mixture (MBM) are two multi-target distributions for which closed-form filtering recursions exist. The PMBM has a Poisson birth process, whereas the MBM has a multi-Bernoulli birth process. This paper considers a recently developed formulation of the multi-target tracking problem using a random finite set of trajectories, through which the track continuity is explicitly established. A multi-scan trajectory PMBM filter and a multi-scan trajector… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 47 publications
0
27
0
Order By: Relevance
“…For a fair comparison, the Gaussian densities in the MB birth were the same as the Gaussian densities in the PPP birth. All compared trackers process the measurements sequentially, one measurement set after another; comparison with trackers that involve multi-scan data association, see, e.g., [24], [36], [42], [43], is outside the scope of this work.…”
Section: Simulation Studymentioning
confidence: 99%
“…For a fair comparison, the Gaussian densities in the MB birth were the same as the Gaussian densities in the PPP birth. All compared trackers process the measurements sequentially, one measurement set after another; comparison with trackers that involve multi-scan data association, see, e.g., [24], [36], [42], [43], is outside the scope of this work.…”
Section: Simulation Studymentioning
confidence: 99%
“…The above track building problems can be solved by computing (multi-object) densities on sets of trajectories [23], rather than sets of labelled targets. This approach has led to the following filters: trajectory PMBM (TPMBM) filter [25], [26], trajectory MBM (TMBM) filter [27], trajectory MBM 01 (TMBM 01 ) filter [23], and trajectory PHD (TPHD) and CPHD (TCPHD) filters [28]. These filters are analogous to their set of targets counterparts, but have the ability to estimate trajectories from first principles, and the possibility of improving the estimation of past states in the trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…The PMBM conjugate prior [25] was originally developed for point targets; a PMBM conjugate prior for extended targets was presented in [3], [4]. In several simulation studies it has been shown that, compared to tracking filters built upon labeled random finite set (RFS), the PMBM conjugate prior has good performance for tracking the set of present target states, for both point targets [26]- [28] and extended targets [3], [4], [29]. The PMBM conjugate priors for point targets and extended targets have been shown to be versatile, and have been used with data from Lidars [30]- [33], radars [31], [32], and cameras [32], [34].…”
Section: Introductionmentioning
confidence: 99%